2008
DOI: 10.1097/mcg.0b013e31815853e0
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Versus Self-expanding Metallic Stents for Malignant Hilar Biliary Obstruction

Abstract: Metallic stent performance was superior to plastic for hilar tumor palliation with respect to short-term outcomes, independent of disease severity, Bismuth class, or drainage quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
150
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(155 citation statements)
references
References 33 publications
3
150
1
1
Order By: Relevance
“…No difference between the patency of straight and pigtail plastic stents was seen, nor was there a difference between unilateral and bilateral plastic stents or SEMS. All re-interventions were performed endoscopically, nine patients with plastic stents were converted to SEMS and plastic stents were placed within SEMS in four patients.The results of Raju et al are similar to those of prior studies identifying less stent failure with the use of SEMS versus plastic stents for hilar tumors [2,3]. There is scant information in the way of randomized comparisons between plastic and metal stents.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…No difference between the patency of straight and pigtail plastic stents was seen, nor was there a difference between unilateral and bilateral plastic stents or SEMS. All re-interventions were performed endoscopically, nine patients with plastic stents were converted to SEMS and plastic stents were placed within SEMS in four patients.The results of Raju et al are similar to those of prior studies identifying less stent failure with the use of SEMS versus plastic stents for hilar tumors [2,3]. There is scant information in the way of randomized comparisons between plastic and metal stents.…”
supporting
confidence: 61%
“…The results of Raju et al are similar to those of prior studies identifying less stent failure with the use of SEMS versus plastic stents for hilar tumors [2,3]. There is scant information in the way of randomized comparisons between plastic and metal stents.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…External drainage, external-internal drainage and metallic stenting are choices for palliation in the percutaneous approach. In a previous prospective, multicenter, observational cohort study, metallic stenting was found to be superior to plastic stenting for hilar malignant biliary obstructions with respect to short-term results (18). In a study by Wagner et al (19), success and patency rates were found to be better for metallic stents than for plastic stents in patients with hilar malignant biliary obstructions.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that SEMS outperformed plastic stents allowing higher rates of successful drainage, prolonged patency, and lower adverse outcomes such as cholangitis, stent migration, etc. [5,6]. The adequacy of unilateral or bilateral drainage continues to be debated [7,8].…”
mentioning
confidence: 99%